O trabalho com a construção do sentido em língua portuguesa (L2) no ensino-aprendizagem de surdos - Jimenez e Silvestre, Carolina de Oliveira [UNIFESP] (2015)
The present research discusses the teaching and learning of Portuguese as a second language (L2) for deaf users of Libras (Brazilian Sign Language) in bilingual perspective, which involves taking founded on the specific language of the deaf culture in reflective activities involving the L2.The theoretical basis of this paper focus on working on the knowledge of the lexicon of Portuguese Speaking from the perspective of enunciation, based on the assumptions of the Theory of Enunciative Operations (TEO), which is the framework directed to the study of language and cognitive operations mobilized in the textual production of meaning. The aim of this study is to contribute to the development of production and textual compreehension in Portuguese language for deaf children, specifically regarding the work of lexical units of verbal nature in its variety of uses. Therefore, we started this research contextualizing topics related to deafness, such as the culture and deaf identity, the educational background drawn to understand deaf population, and also, aspects of sign language. Then, we compare and relate the linguistic study in both linguistic forms e.g., L1 (Libras ? Brazilian Sign Language) and L2 (Portuguese Language), in order to understand the specificities of L1, and through this understanding we reflect on bilingualism and the teaching of L2 to deaf learners. After this discussion we present the principles of the theoretical current in which we rely on, reflecting on the functioning of verbal unit in L1 and L2, the latter by comparing the different strands which study the verbs in Portuguese. Finally, based on the Theory of Enunciative Operations, we discuss methodological issues directed to the study of the meaning of verbal units, L2, with deaf people. The analytical methodology is guided in reformulation practices of various statements which integrate the verb TO BREAK, corpus collected in textual bases and scholarly articles devoted to this lexical unit. We seek, firstly, to show that the word is not defined by a base direction that is inherent; secondly, that the semantic identity comes from the interaction with the statements that helps build it, therefore, the meaning is stabilized by and in its different forms of use; thirdly, that the teaching supported in this identity, by exposing the linguistic operating logic of the verb, is of great interest for learning L2. And yet, as a pedagogical proposal for teaching L2, we suggest a didactic sequence to work with the meaning of the word TO BREAK in classroom for deaf learners. As a result, we hope to show that the teaching and learning of vocabulary cannot be based on activities that focus on a pre-existing meaning and intrinsic to the linguistic unity, therefore, we must rethink the methodologies directed to the lexical work in L2, through expository recast proposals that enable reflection of deaf people on the process of construing the meaning in Portuguese language.